REPRESENTATION OF FEMINISM IN THE MAIN CHARACTERS OF THE FILMS "MALEFICENT MISTRESS OF EVIL" AND "FROZEN 2" - Nia Kurniawati (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Abstract: Fairy Tale films do not only show entertainment for the audience but also therepresentation of femininity that can affect the mindset of the viewers. The representation shouldevolve in line with the global feminist movement in order for the audience to have a realisticdescription of the condition of women in the current era. Research is needed to determine whetherthe transition is in line with the development of feminism waves and theories. This study usesfeminist theories and concepts of femininity as a reference. The primary data collection wascompleted using observation and secondary data was taken from the study of literature anddocumentation. Observations were accomplished by watching Maleficent 2, and Frozen 2 films. Thefinal analysis shows that the transition in the representation of femininity in Maleficent 2, andFrozen 2 films indicates equalities and emphasizes the rebellious side of woman.Keywords: Maleficent 2; Frozen 2; Feminism; Femininity, Representation; Equalities